2006
DOI: 10.2486/indhealth.44.302
|View full text |Cite
|
Sign up to set email alerts
|

Air Conditioning Systems as Non-Infectious Health Hazards Inducing Acute Respiratory Symptoms

Abstract: The risk of air conditioners as potential sources of contaminated aerosols is known for a long time. Recently, the appearance of the severe acute respiratory syndrome caused by a novel SARS coronavirus (SARS-CoV) highlighted the dangers of airborne infectious agents [1][2][3] In this respect, the legionella pneumophila associated pneumonia 4) , even in large public places such as the Picadilly Circus in London 5) or lethal pulmonary aspergillosis 6) have been reported. Therefore, to protect patients from air c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Some health hazards may be transmitted through AC systems, especially if the systems are poorly maintained. 2729 …”
Section: Discussionmentioning
confidence: 99%
“…Some health hazards may be transmitted through AC systems, especially if the systems are poorly maintained. 2729 …”
Section: Discussionmentioning
confidence: 99%
“…[ 16 17 ] The higher prevalence of respiratory symptoms in our study is in line with the results of other studies. [ 18 19 ] Cold dry air from the ACs causes activation of the epithelium to generate pro-inflammatory substances and engorgement of venous sinuses in the submucosa which leads to congestion, sneezing, and rhinorrhea. Repeated cooling and desiccation of peripheral airways can cause airway remodeling similar to that seen in asthma.…”
Section: Discussionmentioning
confidence: 99%
“…There is a potential for transmission of toxic volatile substances via an air conditioning system. In a study done by Gerber et al .,[ 19 20 ] low dose exposure to volatile chemicals by the air conditioning system induced an acute asthma attack and suggested that air conditioning can lead to incidents of inhalation occupational exposure/intoxication to other employees in the same building.…”
Section: Discussionmentioning
confidence: 99%